Towards a unified performance based characterisation of bitumen and mastic using the DSR. (1st June 2021) - Rochlani, Mrinali; Falla, Gustavo Canon; Leischner, Sabine; Wellner, Frohmut
Abstract : A laboratory study was done on three bitumen of penetration grade 50/70 from three sources and three corresponding mastics made using these three base bitumen and one filler – Limestone. The tests were all done using the Dynamic Shear Rheometer (DSR), including frequency sweeps for rheology, single stress creep recovery test (SSCR) for permanent deformation behaviour, Dresden cryogenic test (DDCT) for low temperature performance, and fatigue testing using column specimen. The frequency sweep data was modelled using the 2 Spring-2 Parabolic-1 Dashpot (2S2P1D) rheological model. Selected tests were carried out on unaged and aged bitumen and mastic samples to investigate the sensitivity of the materials to ageing. Performance diagrams were made which could enable in bitumen and mastic selection based on specified desired criteria. It was found that bitumen from different bitumen producers and provenances had different performance behaviours. Furthermore, the addition of the limestone filler also affect the ranking based on specified behaviours.